Description of Complementary Feeding Under-Five Children with the Incidence of Stunting - Lingga, Rugun Togianur; Sihombing, Lentina; Silaban, Jojor; Silaban, Verawaty Fitrinelda (Universitas Prima Indonesia, 2024)
The government has made various efforts to reduce the incidence of stunting in children under five, but to date, it has not shown maximum results. Stunting is a condition where a child has a shorter height than children of the same age, which means that the child's height is below the normal value. Efforts are made to reduce the prevalence of stunting, among others, by monitoring child growth and development, organizing supplementary feeding activities, or providing MP-ASI. Complementary feeding is food or drink that contains energy and nutrients given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. The purpose of the study was to determine the description of complementary feeding in under-fives with the incidence of stunting. This study used descriptive quantitative research methods with a population of 43 stunted clowns using a total sampling technique. The results showed that the description of the provision of complementary foods for stunting was mostly lacking (69.7%) and the incidence of stunting showed a short category (76.7%) and very short (23.3%). Suggestions. Provide health education about complementary feeding for infants and health education about stunting to parents, especially mothers.